2016
DOI: 10.1136/tobaccocontrol-2016-053096
|View full text |Cite
|
Sign up to set email alerts
|

Long-term e-cigarette use and smoking cessation: a longitudinal study with US population

Abstract: BackgroundE-cigarettes have grown popular. The most common pattern is dual use with conventional cigarettes. Dual use has raised concerns that it might delay quitting of cigarette smoking. This study examined the relationship between long-term use of e-cigarettes and smoking cessation in a 2-year period.MethodsA nationally representative sample of 2028 US smokers were surveyed in 2012 and 2014. Long-term e-cigarette use was defined as using e-cigarettes at baseline and follow-up. Use of e-cigarettes only at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
128
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(149 citation statements)
references
References 34 publications
16
128
4
1
Order By: Relevance
“…This is consistent with findings from another study in which roughly one quarter to one half of e-cigarette users reported the belief that e-cigarettes have no health risks. 26 Marketing contributes to perceived knowledge regarding the health and safety of e-cigarettes 28 , and in our sample, participants heard about e-cigarettes from the media, family or friends, and e-cigarette (vape) shops, but very few heard about them from physician offices, which is consistent with other research. 29 These findings underscore the need for PCPs to be able to provide patients with accurate information on these products rather than relying on potentially biased and profit-driven sources of information.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with findings from another study in which roughly one quarter to one half of e-cigarette users reported the belief that e-cigarettes have no health risks. 26 Marketing contributes to perceived knowledge regarding the health and safety of e-cigarettes 28 , and in our sample, participants heard about e-cigarettes from the media, family or friends, and e-cigarette (vape) shops, but very few heard about them from physician offices, which is consistent with other research. 29 These findings underscore the need for PCPs to be able to provide patients with accurate information on these products rather than relying on potentially biased and profit-driven sources of information.…”
Section: Discussionsupporting
confidence: 80%
“…More than one third of our primary care respondents had previously tried or were currently using e-cigarettes, consistent with the rising use of e-cigarettes use in the US. [1][2][3][4][5]26 However, 18% of the e-cigarette users had never smoked cigarettes, suggesting that some adults may be trying e-cigarettes for reasons other than to stop or reduce smoking.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a longitudinal study found that US smokers who used e-cigarettes over two years had a higher rate of quit attempts and cessation rate than short-term e-cigarette users or non-users. 24 E-cigarettes may also help smokers to reduce the number of cigarettes smoked. 25,26 Conflicting information may therefore deter smokers from switching to a potentially less harmful product if they are unable to quit using conventional treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Analysing US data from the 2014 and 2015 National Health Interview Surveys, Giovenco and Delnevo found that among adults who had smoked in the past 5 years, daily vaping was the factor most strongly associated with smoking cessation 12. Longitudinal data reported by Zhang et al found that long-term vaping (at least 2 years) was associated with a fourfold higher odds of quitting than among non-users, adjusted for baseline characteristics of the sample 13. Biener and Hargreaves also observed that daily vaping for at least a month was associated with sixfold greater odds of quitting smoking in another longitudinal study 14.…”
mentioning
confidence: 99%